D-index dose not predict the development of pulmonary infection in acute myeloid leukemia patients undergoing consolidation chemotherapy with high-dose cytarabine. Issue 2 (March 2014) - Kimura, Shun-ichi; Wada, Hidenori; Ishihara, Yuko; Kawamura, Koji; Sakamoto, Kana; Yamasaki, Ryoko; Ashizawa, Masahiro; Machishima, Tomohito; Sato, Miki; Terasako, Kiriko; Nakasone, Hideki; Kikuchi, Misato; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> The D-index is calculated as the area over the neutrophil curve during neutropenia. We investigated the impact of the D-index on pulmonary infection in 33 acute myeloid leukemia patients undergoing consolidation chemotherapy with high-dose cytarabine. There was no difference in the D-index between chemotherapies with and without pulmonary infection. The cumulative D-index (c-D-index) until the development of infection exceeded 4000 in four of five patients with pulmonary infection. Although there was no difference in the total D-index throughout the overall consolidation chemotherapy, the total D-index from induction to consolidation and the D-index at induction chemotherapy were higher in patients with pulmonary infection during consolidation than in those without it (P = 0.014 and 0.019, respectively). Our results showed that the cumulative effect of neutropenia might determine the risk of pulmonary infection in consolidation chemotherapy. We are planning a clinical trial of c-D-index-guided preemptive antifungal therapy.